Swimming in the Ecuadorian school and extracurricular sport: A proposal of Curricular Improvement/La natación en el deporte escolar y extracurricular ecuatoriano: una propuesta de mejoramiento curricular - Roberto Javier Terán Díaz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
Physical Education is committed to the integral formation, balance and well-being of the student and, within this, swimming, as a practice of exercises in the aquatic environment, promotes curricular improvement in the processes of updating and strengthening the area. The objective of this research was to present a proposal for the curricular improvement of swimming. The empirical methods of the bibliographic review were applied to 20 published documents, from 2007 to the present of the databases of Google Academic and the Platform of the Ministry of Education of Ecuador and the interview applied to 10 expert swimming trainers of the city of Quito in Ecuador. A critical and synthetic analysis was carried out in two stages; the first was dedicated to the development of the swimming curriculum in Physical Education and the second to swimming as a physical and sports practice. This helped to reach an understanding of the socio-educational-curricular fact and its real concreteness in the curricular development of swimming in Ecuadorian Physical Education. In addition, a gap was found that allowed the proposal to be justified in three aquatic domains, linked to the essential basic curricular skills, which could standardize learning in this environment, from the use of the swimming pool as a resource and swimming as a new recreational sport practice for life.